Public Service Motivation and Attrition: Studying Individual-Level Turnover Behavior in the Public Sector Using Panel Data - Michael Bednarczuk (Journal of Public and Nonprofit Affairs)
One of the foundational claims of public service motivation (PSM) is that it should influence an individual's willingness to join and remain in public organizations. However, the evidence in support of the “attrition hypothesis” is nuanced, and there is a lack of research examining actual turnover behavior. This study addresses this gap by using longitudinal data from the Youth-Parent Socialization Study to examine the relationship between pre-employment PSM-related values and long-term turnover behavior in the public sector. A multinomial logit model finds that those with higher PSM-related values in childhood are more likely to remain employed in the public sector over time. These results have practical implications for public sector retention strategies, as fostering the development of PSM-related values could lead to reduced employee churn and their related costs.